PERJANJIAN CARTER KAPAL DALAM PRAKTEKNYA ANTARA PT. SABANG RAYA INDAH DENGAN PENYEWA DI KOTA JAMBI - Fadlan Zamzimi (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
In the world of commerce, trade done well in domestic and overseas trade, sea transportation problem is one very important factor in supporting the smooth flow of goods, while also contributing to transport people who want to visit a single country with others as well as from city to city the other cypress.Given the role of sea transport as mentioned above, then the increase fluency by the entrepreneur freight (shipping company) has provided a pen chartered ship, both ships chartered by time (time charter) or travel by boat charter (voyage charter) for the parties need it.Keyword : The agreement, Carter Boat, Renters